National Neighborhood Crime Study, Wave 2 (NNCS2), (United States), 1999-2013 - Krivo, Lauren J. ([Verlag nicht ermittelbar], 2022)
The primary purpose of the second wave of the National Neighborhood Crime Study (NNCS2) was to develop a panel dataset of serious reported crimes in urban neighborhoods circa two time points - 2000 and 2010. These data offer the opportunity to assess the sources and consequences of neighborhood crime change for "communities" of different ethno-racial and economic compositions across the United States. The study also sought to examine the role of a neighborhood's broader ecology on crime levels and crime change by integrating indicators of city and/or metropolitan conditions. The NNCS2 includes two datasets. The first dataset, the NNCS2-Panel file (NNCS2-P), contains information on the Federal Bureau of Investigation's (FBI) Part 1 Index crimes (except arson), socioeconomic and demographic characteristics, and a variety of other neighborhood and city level controls for circa 2000 and 2010 for tracts in 81 of the 91 cities in the NNCS, wave 1. The second dataset, the NNCS2-Cross-Sectional file (NNCS2-CS), allows for examination of the local and contextual sources of neighborhood crime inequality circa 2010. The NNCS2-CS incorporates parallel data for census tracts and cities as in the Panel file, but includes a few additional cities for which panel data could not be compiled, as well information on the metropolitan areas within which cities are located.